Design And Development Of A Quality And Quantity Water Monitoring System For Water Tank Based On Internet Of Things - Abdullah Rayni; A M H Pardede; Hasanul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
In the context of urban life, the quality and quantity of water stored in tanks play an indispensable role. However, concerns over the lack of effective monitoring of water conditions in tanks have garnered significant attention. This research aims to design a monitoring system utilizing Internet of Things (IoT) technology to ensure continuous monitoring of water quality and quantity within tanks. The study zeroes in on developing a solution that overcomes the limitations of traditional methods, known for their time and cost constraints. This solution hinges on a real-time monitoring system that integrates sensors and the NodeMCU ESP32 microcontroller. Measurements of water quality parameters, such as turbidity and total dissolved solids (TDS), along with assessments of water quantity through tank volume, are integrated into the system. Software development is carried out using the Arduino IDE platform. Through this research, an increased awareness of the importance of monitoring water quality in tanks is anticipated, and this solution is expected to make a significant contribution to the development of efficient and effective monitoring technology. Thus, a crucial step toward more accurate and up-to-date water monitoring in urban environments can be achieved.